PENGARUH MEDIA E-FLASHCARD TERHADAP KEMAMPUAN KOSAKATA BAHASA INGGRIS ANAK USIA 5-6 TAHUN DI TK TUNAS RIMBA PALEMBANG (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using e-flashcard media on improving English vocabulary of children aged 5–6 years at PAUD Tunas Rimba Palembang. This research used a quantitative approach with a pre-experimental design, namely one group pretest-posttest design. The sample consisted of 16 children aged 5–6 years. Data collection techniques were carried out through tests in the form of pretest and posttest based on five indicators of vocabulary ability. The results showed that there was an increase in the average score from 9.31 in the pretest to 16.75 in the posttest. Furthermore, the hypothesis test using the Wilcoxon Signed Rank Test obtained a significance value of 0.000 < 0.05, indicating a significant effect of the use of e-flashcard media on children's English vocabulary ability. The findings also showed that children's development category improved from “Beginning to Develop” to “Developing as Expected” and “Very Well Developed.” Thus, e-flashcard media is proven to be effective in improving English vocabulary of early childhood through interactive and engaging learning activities.